2013
DOI: 10.1021/jp402250v
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility Transistors Based on Single Crystals of Isotopically Substituted Rubrene-d28

Abstract: We have performed a comprehensive study of chemical synthesis, crystal growth, crystal quality, and electrical transport properties of isotopically substituted rubrene-d 28 single crystals (D-rubrene, C 42 D 28 ). Using a modified synthetic route for protonated-rubrene (H-rubrene, C 42 H 28 ), we have obtained multigram quantities of rubrene with deuterium incorporation approaching 100%. We found that the vaporgrown D-rubrene single crystals, whose high qualities were confirmed by X-ray diffraction and atomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
79
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 46 publications
7
79
1
Order By: Relevance
“…46 However, in 1973, they overturned this result and reported a 10% negative IE in the c 0 direction and zero effect in the a and b directions. 7 We recently proposed using the IE effect to probe the quantum nuclear tunneling effect in organic semiconductors such as N,N 0 -n-bis(n-hexyl)-naphthalene diimide (NDI) and N,N 0 -n-bis(n-octyl)-perylene diimide (PDI). 19 Very recently, Frisbie et al reported a negligible IE for hole transport in all-deuterated rubrene.…”
Section: Introductionmentioning
confidence: 99%
“…46 However, in 1973, they overturned this result and reported a 10% negative IE in the c 0 direction and zero effect in the a and b directions. 7 We recently proposed using the IE effect to probe the quantum nuclear tunneling effect in organic semiconductors such as N,N 0 -n-bis(n-hexyl)-naphthalene diimide (NDI) and N,N 0 -n-bis(n-octyl)-perylene diimide (PDI). 19 Very recently, Frisbie et al reported a negligible IE for hole transport in all-deuterated rubrene.…”
Section: Introductionmentioning
confidence: 99%
“…Additional examples of organic-based devices with high mobilities include the work by Podzorov et al in 2003, who demonstrated a mobility magnitude of 8 cm 2 /Vs by optimizing the fabrication process of rubrene-based single-crystal organic field-effect transistors [24] . A decade later, Wei Xie et al showed a transistor based on rubrene-d28 single crystals with a consistent mobility of 10 cm 2 /Vs at room temperature [25] , and in the same year, Il Kang et al built an OTFT with a mobility of 12 cm 2 /Vs through side-chain engineering of two polymer semiconductors (P-29-DPPDBTE and P-29-DPPDTSE) [26] . Note that predominant organicbased devices are p-type and thus the reported mobilities correspond to holes; electron mobilities are usually several factors lower (the highest electron mobility of 6.3 cm 2 /V.s reported was achieved with the donor-acceptor polymer PDBPyBT by Bin Sun et al) [27] .…”
Section: Devices Challenges and Applications Of Organic Electronicsmentioning
confidence: 99%
“…SCFETs were fabricated and showed ambipolar transport as expected. Although device architecture has not been fully optimized, maximum hole (electron) mobilities [43]. The X ray diffraction data indicate that the D rubrene maintains the same crystal structure and unit cell parameters as the H rubrene crystal.…”
Section: Rubrene and Its Derivativesmentioning
confidence: 99%